Simulasi Model Fisik Untuk Analisis Karakteristik Gelombang Pecah Pada Pantai Bergambut - Milka Novita Manalu; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The coastal area of Bengkalis Regency, especially the one directly opposite the Malaka Strait has the characteristic of sea waves that are strong enough so that it can suffer quite severe damage such as abrasion and sedimentation. Abrasion and sedimentation on the coast is influenced by the characteristic wave conditions. The purpose of this research is to make a beach modeling to determine the characteristics of breaking waves and to compare the breaking waves on peat, clay and sandy beaches. The method used in this research is wave simulation by making peat beach modeling with scale variations of 2,3,4,5 and 6 on the wave generator. This simulation uses laboratory simulation. The results showed that the height of the breaking waves on a clay beach is 0.017 to 0.034 m, the depth of breaking waves is 0.003 to 0.033 m and the types of breaking waves that occurred were spilling and plunging. The height of the breaking waves of sand material is 0.012 to 0.033 m, the depth of breaking waves is 0.010 to 0.031 m and the types of breaking waves that occurred were spilling and plunging. The height of the breaking waves of the peat material is 0.008 to 0.025 m, the depth of breaking waves is 0.008 to 0.025 m and the types of breaking waves that occurred were spilling and plunging. Keywords : peat, coast, breaking wave